Tualang Honey Supplementation Alleviates Obesity and Dyslipidaemia in High Cholesterol Diet Induced Non-Alcoholic Steatohepatitis Animal Model - Alias, Mohd Afzal; Abdul Rahim, Roslina; Muhamad, Siti Aesah @ Naznin; Abdullah, Nor Zamzila; A Talib, Norlelawati; Ahmad Affandi, Khairunisa (IIUM Medical Journal Malaysia, 2022)
INTRODUCTION: Dyslipidaemia and obesity are two main features of non-alcoholic steatohepatitis (NASH). This study aimed to investigate the effects of Tualang honey (TH) supplementation on bodyweight, liver weight, and lipid profiles in high cholesterol diet (HCD) induced NASH animal model. MATERIALS AND METHODS: Sixteen Sprague-Dawley rats were given 12% HCD for 16 weeks to induce NASH. These animals were divided into 4 groups; Group 1 (continued HCD), Group 2 (changed to normal diet), Group 3 (normal diet and TH 1.2g/kg) and Group 4 (normal diet and TH 3.0g/kg) for the following 4 weeks. Bodyweight was measured daily. At the end of the study, blood was collected via retro-orbital bleeding and the rats were sacrificed to harvest their liver. RESULTS: The group 4 rats had significantly lower mean final bodyweight than rats in group 1, 2 and 3 (478.0±24.4 vs. 641.5±25.1, 593.8 ±29.3, 552.0±72.9 g, p<0.05). Animals in group 4 were also found to have a significantly lower mean liver weight compared to groups 1 and 2 (12.9±0.9 vs 20.1±2.2, 15.7±1.2 g, p<0.05). In comparison to controls, the mean concentration of total cholesterol was significantly lower in all the other groups and the lowest mean concentration of triglycerides was recorded in group 4 with significant difference when compared to the controls (0.9±0.4 vs 3.6±0.4 mmol/L, p<0.05). CONCLUSION: The change from HCD to a normal diet coupled with TH supplementation has been shown to reduce bodyweight, liver weight, total cholesterol and triglyceride levels in the 12% HCD NASH induced animal models.